Pengaruh Indomaret Terhadap Pendapatan Pedagang Kecil di Kelurahan Pabiringa Kabupaten Jeneponto - Maksud Hakim; Anna Sulfianti; Rini Kartini (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of Indomaret on the income of small traders in Pabiringa Village, Jeneponto Regency. The method used is simple linear regression analysis with the F Test, and the data is processed using SPSS version 18. The results show that there is a significant influence between the existence of Indomaret on the income of small traders, with a linear equation Y = 2.170 + 0.039X. The coefficient of determination (R square) of 0.551 indicates the strength of the influence.